PENGGUNAAN TECHNOLOGY ACCEPTANCE MODEL DALAM MEMAHAMI NIAT PERILAKU USAHAWAN UNTUK MENGGUNAKAN E-COMMERCE SAAT PANDEMI COVID-19 - Mardiah, Fatma Poni; Rahmi, Devi Yuli (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The tourism industry is a sector that has clearly been affected by the impact of COVID-19. Since the implementation of the Large-Scale Social Restrictions (PSBB), all tourist attractions have automatically been closed. The decrease in visitors to tourist destinations has had an impact on Micro, Small, and Medium Enterprises (UMKM) that rely on the tourism sector. The UMKM referred to here are souvenir shops that are usually frequented by tourists. One solution for them to survive is to market their products through e-commerce. This research uses the explanatory research method, employing primary data obtained through a questionnaire. The respondents of this study are business owners or managers of souvenir shops in the city of Payakumbuh and the district of Lima Puluh Kota. The sampling was done using the convenience sampling method, and the determination of the minimum sample size was assisted by the Gpower tool (statistical power level of 85%, with a minimum sample requirement of 115 samples). Data analysis was conducted using partial least squares with the assistance of the SMART PLS V 3.3.3 tool. The research findings indicate that the perception of ease of use and the perception of the usefulness of technology have a significant positive effect on the attitude toward technology acceptance and also have a positive effect on the intention to use technology. The implications of this research show that entrepreneurs who perceive difficulties in conducting business activities with e-commerce will not use technology even in a forced situation. Industri pariwisata merupakan sektor usaha yang terlihat jelas terkena dampak COVID-19. Sejak diberlakukannya PSBB, otomatis semua tempat wisata ditutup. Berkurangnya pengunjung tempat wisata berdampak pada UMKM yang hidup dari sektor pariwisata. UMKM yang dimaksud adalah UMKM pusat oleh-oleh yang biasanya ramai dikunjungi wisatawan. Salah satu solusi agar mereka dapat tetap bertahan adalah dengan memasarkan produknya melalui ecommerce. Penelitian ini menggunakan metode explanatory research dimana menggunakan data primer yang didapatkan dengan kuesioner. Responden penelitian ini adalah pemilik usaha atau manager pusat oleh-oleh di Kota Payakumbuh dan Kabupaten Lima Puluh Kota. Pengambilann sampel dengan metode convenience sampling dan penentuan jumlah sampel minimal dengan bantuan tools Gpower (tingkat statistical power 85% kebutuhan sampel minimum sebanyak 115sampel)(Erdfelder et al., 2009). Analisis data dengan partial least square dengan bantuan tools SMART PLS V 3.3.3. Hasil penelitian menemukan bahwa persepsi kemudahan penggunaan, persepsi kebermanfaatan teknologi berpengaruh positif signifikan terhadap sikap penerimaan teknologi dan juga berpengaruh positif terhadap niat menggunakan teknologi. Implikasi penelitian ini menunjukan usahawan yang merasakan kesulitan melakukan aktivitas usaha dengan ecommerce tidak akan menggunakan teknologi walaupun dalam situasi terpaksa.